Dziedzictwo kulturowe. Edukacja. Historia. Dziedzictwo regionalne. Muzyka, literatura, sztuka i media - Ratajczak, Krzysztof; Konstańczak, Marta; Sendor, Albert; Kontowski, Daniel; Antonik, Aleksandra; Koperski, Łukasz; Mazurkiewicz, Mariusz; Prabucki, Bartosz; Kruszyńska, Agnieszka; Staśkiewicz, Helena; Żywicka, Anna; Buchwald, Anna; et al. (My University, 2015)
The following publication showcases research on national heritage by early career researchers from Poland. Articles included are related to the broad domain of pedagogy, spanning over social sciences or arts and humanities. Contributions represent both historical and contemporary insights from a range of disciplines: education, history, area studies, art and media studies. Various examples of national heritage are discussed from both Polish and general perspective. The aim of the book was to contribute to the process of inclusion of new researchers into interdisciplinary and intergenerational dialogue.
Keywords: History of Education; Innovations in Education; National Heritage